IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DI 10 DESA WILAYAH KECAMATAN REMBANG KABUPATEN REMBANG - Prasetyo, Yudhi; N. Masdjojo, Gregorius (Proceeding SENDI_U, 2015)
Implementation of Policy of ADD in Subdistrict of Rembang of Regency of Rembang have walked enough is fluent.But that way if hooked;correlated farther with attainment of target of execution of Allocation of Countryside Fund (ADD) in Subdistrict of Rembang of Regency of Apex still not yet optimal. As for factors influencing execution ofADD in Subdistrict of Rembang of Regency of Rembang cover communications, resource ability, executor attitude,bureaucracy structure, environmental and also size measure and policy target. Among/Between the factors, result ofthis research lay open that factor of ability of sumberdaya and also factor of size measure and target of very strongpolicy have an effect on to implementation of policy of policy of ADD in Subdistrict of Rembang of RembangRegency.Keyword : Allocation of Countryside Fund, Resource Ability, Executor Attitude, Bureaucracy Structure.